Early Academic Success in College: Examining the Contributions of Reading Literacy Skills, Metacognitive Reading Strategies, and Reading Motivation. Issue 1 (2nd January 2023) - Talwar, Amani; Magliano, Joseph P.; Higgs, Karyn; Santuzzi, Alecia; Tonks, Stephen; O'Reilly, Tenaha; Sabatini, John
ABSTRACT: More knowledge is needed regarding the student factors that impact academic reading and success in college beyond traditional measures of college readiness. This study examined the contributions of student factors specified by the Proficient Academic Reader framework—reading literacy skills, metacognitive reading strategies, and reading motivation—to performance on a complex academic reading task and cumulative GPA across three semesters within the first two years of college. Hierarchical regression models were estimated using a sample of 166 students at a four-year public institution. Results indicated the importance of vocabulary, reading comprehension, and problem-solving reading strategies to academic reading performance and early college GPA. However, some of these effects diminished after controlling for students' standardized test scores and high school GPA. The findings imply that institutions should implement sustained support for reading skills and strategies across disciplines.